Al-TahlÄ«l al-WasfÄ« â€˜an MawÄd MahÄrah al-KalÄm fÄ« KitÄb DurÅ«s al-Lughah al-Ê¿Arabiyyah li Manhaj 2013 - Nasuha, Ali; Sepputri, Elsa (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2023)
The background of this research is because there is a discrepancy between the arrangement of kalam material in Class 1 Arabic Language Books at Madrasah Ibtidaiyah and the standard presentation of kalam material by Abdurrahman bin Ibrahim al-Fauzan. Therefore, this study aims to see the suitability of the preparation of kalam material in Class 1 Arabic Language Books at Madrasah Ibtidaiyah with Abdurrahman bin Ibrahim al-Fauzan's standard of presentation of kalam material. The research methodology to descriptive Content Analysis. From the results of the analysis of the kalam material in the Class 1 Arabic Book of Madrasah Ibtidaiyah, the result is that the kalam material in the Arabic book is in accordance with the standard of presentation of the kalam material, but still requires improvement in certain parts, and the content of the existing material. appropriate to the level of student needs. If the writing of this book refers to the standards that have been prepared by Ibrahim Fauzan, then this book will be easy for students to understand and easy to apply.ØªØ¹ÙˆØ¯ Ø®Ù„ÙÙŠØ© Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø¥Ù„Ù‰ ÙˆØ¬ÙˆØ¯ ØªÙ†Ø§Ù‚Ø¶ Ø¨ÙŠÙ† ØªØ±ØªÙŠØ¨ Ù…Ø§Ø¯Ø© Ø§Ù„ÙƒÙ„Ø§Ù… ÙÙŠ ÙƒØªØ¨ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ù„ØµÙ Ø§Ù„Ø£ÙˆÙ„ ÙÙŠ Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø§Ø¨ØªØ¯Ø§ÙŠØ© ÙˆØ§Ù„Ø¹Ø±Ø¶ Ø§Ù„Ù‚ÙŠØ§Ø³ÙŠ Ù„Ù…Ø§Ø¯Ø© Ø§Ù„ÙƒÙ„Ø§Ù… Ù„Ø¹Ø¨Ø¯ Ø§Ù„Ø±ØÙ…Ù† Ø¨Ù† Ø¥Ø¨Ø±Ø§Ù‡ÙŠÙ… Ø§Ù„ÙÙˆØ²Ø§Ù†. Ù„Ø°Ù„ÙƒØŒ ØªÙ‡Ø¯Ù Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¥Ù„Ù‰ Ù…Ø¹Ø±ÙØ© Ù…Ø¯Ù‰ Ù…Ù„Ø§Ø¡Ù…Ø© ØªØØ¶ÙŠØ± Ù…Ø§Ø¯Ø© Ø§Ù„ÙƒÙ„Ø§Ù… ÙÙŠ ÙƒØªØ¨ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ù„ØµÙ Ø§Ù„Ø£ÙˆÙ„ Ø¨Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø§Ø¨ØªØ¯Ø§ÙŠØ© Ù…Ø¹ Ù…Ø¹ÙŠØ§Ø± Ø¹Ø¨Ø¯ Ø§Ù„Ø±ØÙ…Ù† Ø¨Ù† Ø¥Ø¨Ø±Ø§Ù‡ÙŠÙ… Ø§Ù„ÙÙˆØ²Ø§Ù† Ù„Ù…ÙˆØ§Ø¯ Ø§Ù„ÙƒÙ„Ø§Ù…. Ù…Ù†Ù‡Ø¬ Ø§Ù„Ø¨ØØ« Ø§Ù„ÙˆØµÙÙŠ Ù„ØªØÙ„ÙŠÙ„ Ø§Ù„Ù…ØØªÙˆÙ‰. Ù…Ù† Ù†ØªØ§Ø¦Ø¬ ØªØÙ„ÙŠÙ„ Ù…Ø§Ø¯Ø© Ø§Ù„ÙƒÙ„Ø§Ù… ÙÙŠ Ø§Ù„ÙƒØªØ§Ø¨ Ø§Ù„Ø¹Ø±Ø¨ÙŠ Ù„Ù„ØµÙ Ø§Ù„Ø£ÙˆÙ„ Ù…Ù† Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø¥Ø¨ØªØ¯Ø§Ø¦ÙŠØ©ØŒ ÙƒØ§Ù†Øª Ø§Ù„Ù†ØªÙŠØ¬Ø© Ø£Ù† Ù…Ø§Ø¯Ø© Ø§Ù„ÙƒÙ„Ø§Ù… ÙÙŠ Ø§Ù„ÙƒØªØ§Ø¨ Ø§Ù„Ø¹Ø±Ø¨ÙŠ ØªØªÙˆØ§ÙÙ‚ Ù…Ø¹ Ù…Ø¹ÙŠØ§Ø± ØªÙ‚Ø¯ÙŠÙ… Ù…Ø§Ø¯Ø© Ø§Ù„ÙƒÙ„Ø§Ù…ØŒ ÙˆÙ„ÙƒÙ†Ù‡Ø§ Ù„Ø§ ØªØ²Ø§Ù„ Ø¨ØØ§Ø¬Ø© Ø¥Ù„Ù‰ ØªØØ³ÙŠÙ† ÙÙŠ Ø¨Ø¹Ø¶ Ø§Ù„Ø£Ø¬Ø²Ø§Ø¡ ÙˆÙ…ØØªÙˆÙ‰ Ø§Ù„Ù…ÙˆØ§Ø¯ Ø§Ù„Ù…ÙˆØ¬ÙˆØ¯Ø©. ØªØªÙ†Ø§Ø³Ø¨ Ù…Ø¹ Ù…Ø³ØªÙˆÙ‰ Ø§ØØªÙŠØ§Ø¬Ø§Øª Ø§Ù„Ø·Ù„Ø§Ø¨. ÙŠØ£Ù…Ù„ Ø§Ù„Ø¨Ø§ØØ« Ø£Ù† ØªÙƒÙˆÙ† ÙƒØªØ§Ø¨ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ù„ØµÙ Ø§Ù„Ø£ÙˆÙ„ Ø§Ù„Ø§Ø¨ØªØ¯Ø§Ø¦ÙŠ Ù„Ù„ØµÙ Ø§Ù„Ø£ÙˆÙ„ Ø§Ù„Ø§Ø¨ØªØ¯Ø§Ø¦ÙŠØ© ÙƒÙ…Ø§Ù„Ø§Ù‹ØŒ Ø¨ØÙŠØ« ØªØµØ¨Ø Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙŠØØ¨ÙˆÙ† Ø§Ù„Ø·Ù„Ø§Ø¨.